THE ENFORCEABILITY AND EFFECTIVENESS OF ANTI-CORRUPTION LAWS IN REDUCING CORRUPTION CASES IN INDONESIA - Kesuma, Derry Angling; Nasir Uddin, Mohammed (Universitas Syiah Kuala, 2024)
The role of the legal system, particularly through the Anti-Corruption Commission (KPK) and other law enforcement agencies in Indonesia, is pivotal in addressing high-profile corruption cases. However, these efforts have been impeded by factors such as political interference, resource limitations, and a lack of anti-corruption culture, posing challenges for the future. This article employs a normative legal research methodology, utilizing statutory and conceptual frameworks. Data collection involved a thorough literature review of relevant laws and regulations related to anti-corruption issues. In this context, the collaboration between the legal system and civil society emerges as a synergistic force in establishing a robust anti-corruption ecosystem. Emphasizing preventive measures like asset declarations and conflict-of-interest regulations offers valuable insights into the proactive role the legal system can assume in averting corruption before it spreads.